James M. Robinson, Tajemnica Judasza: historia niezrozumianego ucznia i jego zaginionej ewangelii, tłum. Jakub Slawik, Warszawa 2006, Nadir Media Lazar, ss. 248. - Zmorzanka, Anna Z. (Vox Patrum, 2007)
review